(3GJLGgGJ RQGY GdehGdM fMh GdecGaMI GdMjhjI dMTQI UGfYI CfaGb ChQGb GdehGdM HGdfhHGQjIs - (3gjcd, SjO YHO GdfHjs; (3MGeO, MfGf SYO GdOjfs; (3YjO, CejQI CMeO CMeOs (2016)
(3GSJgOa GdHMK GdJYQa Ydi OQLI GJLGg GdRQGY GdehGdM fMh GdecGaMI GdMjhjI dMTQI UGfYI CfaGb GhQGb GdehGdM, hJMOjO GdYdGbI Hjf GdeJZjQGJ GdeSJbdI GdeOQhSI hHjf OQLI GJLGg RQGY GdehGdM fMh GdecGaMI GdMjhjI dMTQI UGfYI CfaGb ChQGb GdehGdM, hJMOjO fSH ESgGe cd ef GdeJZjQGJ GdeSJbdI PGJ GdYdGbI GdGQJHGWjI GdeYfhjI aj JaSjQ GdJHGjf Gdcdj dGJLGg RQGY GdehGdM fMh GdecGaMI GdMjhjI dMTQI UGfYI GfaGb GhQGb GdehGdM(B.s
(3jMJhj Ydj eQGLYs
(3edNU HGddZI GdCfLdjRjIs
Keywords: (3GdehGdMs -- (3GeQGV hGaGJs -- (3ecGaMIs -- (3GdfhHGQjI (B((3eUQs